Analisis Khotbah Alkitabiah Berkemenangan Di Dunia Pluralisme - Wiranto, Derry; Sianipar, Rikardo P.; Selviawati, Selviawati (Institut Agama Kristen Negeri Tarutung, 2024)
This research analyzes the challenges of biblical preaching in the context of religious pluralism. The problem discussed is how to address pluralistic understanding that relativizes religious truth and equates all paths to salvation. The research aims to identify winning biblical preaching strategies without compromising the uniqueness of Christianity. The research method uses a qualitative approach with literature study from various relevant sources. The results show that victorious biblical preaching requires proper exegesis, a Christocentric approach, wise contextualization, and dependence on the Holy Spirit. Preachers need to maintain theological integrity while remaining relevant in a pluralistic society.